Intermittent Fasting Could Be Safely Achieved in People With Type 1 Diabetes Undergoing Structured Education and Advanced Glucose Monitoring - Al-Ozairi, Ebaa; El Samad, Abeer; Al Kandari, Jumana; Aldibbiat, Ali M. (Frontiers in Endocrinology, 2019)
Background: Fasting during Ramadan is a form of intermittent fasting in which a person abstains from oral intake between the hours of sunrise and sunset. The fasting month of Ramadan is observed by Muslims worldwide. People with type 1 diabetes (T1DM) who choose to fast during Ramadan are at a particularly high risk of acute diabetes complications including hypoglycemia and significant hyperglycemia. We hypothesized that people with uncomplicated T1DM would be able to fast safely during Ramadan following structured education and with daily advanced glucose monitoring. Methods: People with stable and uncomplicated T1DM treated with multiple daily injections (MDIs) or continuous subcutaneous insulin infusion (CSII) who chose to fast during Ramadan were recruited for the study. Participants attended Dose Adjustment for Normal Eating (DAFNE) structured education training, and basal insulin was reduced in a controlled fashion. Participants were assigned a sensor-augmented insulin pump or FreeStyle Libre for advanced glucose monitoring. The primary endpoint was the rate of hypoglycemia during Ramadan compared to before Ramadan. Secondary endpoints were percentage time spent <4 mmol/L, >10 mmol/L (range, 4–10 mmol/L), episodes of diabetic ketoacidosis, and acute kidney injury or hospitalization for any cause. Results: Rates of hypoglycemia were significantly reduced during Ramadan compared with before Ramadan (0.53 ± 0. 49 vs. 0.81 ± 0.69 episodes/day, p = 0.0015). No episodes of severe hypoglycemia, diabetic ketoacidosis, acute kidney injury, or hospitalization occurred during Ramadan period. Percentage time spent >10 mmol/L (46.7% ± 17.7% vs. 42.5% ± 16.4%, p = 0.03) was significantly increased, and percentage time [range, 4–10 mmol/L (48.8% ± 15.9% vs. 50.9% ± 15.9%, p = 0.13)] and percentage time spent <4 mmol/L (4.7% ± 5.4.7% vs. 5.7% ± 6.3%, p = 0.09) were reduced, but these differences were not significant. Conclusions: People with uncomplicated T1DM could safely participate in intermittent fasting similar to Ramadan fasting if equipped with structured education and advanced glucose monitoring systems.